Cadmium Substitution Effect on Microstructure and Magnetic Properties of Mg-Cu-Zn Ferrites - Beyranvand, Morteza; Zahedi, Ahmad; Gholizadeh, Ahmad (Frontiers in Materials, 2022)
The microstructure, optical, and magnetic properties of CdxMg0.3-xCu0.2Zn0.5Fe2O4 ferrites prepared by the citrate auto-combustion method were investigated. The samples were analyzed by X-ray diffraction, scanning electron microscopy, UV-Vis spectroscopy, X-ray energy-dispersive spectroscopy, Fourier-transform infrared spectroscopy, and vibrating sample magnetometer. Rietveld refinement of XRD patterns shows a single-phase cubic structure (space group Fd3 ̅m) for the samples with x up to 0.20, while the impurity phase of CdO is observed in the samples with x = 0.25, 0.30. As the substitution content increases, the presence of non-magnetic Cd2+ ions in the octahedral site and the migration of Fe3+ions from the octahedral site to the tetrahedral site decreases the saturation magnetization of the samples. Comparison of the bandgap energy of the samples shows an increasing trend with Cd substitution for x up to 0.20 and then decreases, which can be interpreted in terms of changes in the electronic structure of the samples. Improvement in dielectric properties of the samples with increase of Cd2+ content for x up to 0.20 may be attributed to easier transfer and electron exchange between Fe3 + and M2+ ions.